PENERAPAN SISTEM PENGENDALIAN MANAJEMEN BERBASIS SPIRITUALITAS PADA ETNIS MADURA DI UD SELAMAT JAYA - Eva Fuad Aldy; Sujoko Efferin (CALYPTRA, 2018)
Abstract - This study aims to understand the value of Madurese ethnic culture in the management control system applied in UD Selamat Jaya. The control system found was analyzed for weakness based on the point of view of spirituality and its own cultural values.This research is a qualitative researchand use UD Selamat Jaya as research object. The scope of the study is limited only to the internal environment of UD Selamat Jaya whose members of the organization are Madurese. The methods used to obtain data are interview, observation, and document analysis (if possible). The collection process takes place within 3 months. Interview method used is semi-stuctured interviews where some questions have been prepared beforehand but in the process adjust the condition of spontaneity of participants.The research findings show that the object's control system is still informal. Not much Madura cultural value is implemented. Some are done as a habit without conscious understanding. From the angle of spirituality, too, there is not much but it is implied. MCS based on spirituality combined with the meaning of Madurese cultural values can be a solution of weakness analysis. The result of analysis and discussion shows that SPM based on spirituality combined with Madurese cultural values give positive impact to UD Selamat Jaya.